Experimental analysis of particle deposition in fibrous depth filters during gas cleaning using X-ray microscopy. Issue 12 (1st November 2022) - Hoppe, K.; Schaldach, G.; Zielke, R.; Tillmann, W.; Thommes, M.; Pieloth, D.
Abstract: Microscopic data on airborne particle separation in depth filters are a key for understanding and predictive modeling of the evolution of filtration properties such as pressure drop and efficiency during the filtration process. Tomographic imaging techniques (e.g., MRI, CT) are excellent methods for 3D-resolved analysis of microscopic loading behavior, but these are often limited in terms of spatial resolution and because of the low contrast between filter material and particles. In this study, an X-ray microscope was used to analyze the separation of iodine-containing particles (d50, 3 =1.5 µm) in a coarse dust filter (porosity: 0.98; fiber diameter: 24 µm). The use of iodine-containing particles produced sufficient contrast for segmentation and analysis of the particle deposits produced during filtration. The established method allowed the analysis of the deposits within the material in terms of mass, size distribution, and the shape of the formed deposits in time and space. The data presented in this work provide new insights and methods for an improved understanding of the dynamic behavior of filter materials. Graphical Abstract: UF0001